IT-enabled performative spaces in gender segregated work - Alotaibi, Amal (2015)
This thesis investigates the use of ICT in Saudi Arabia to support collaboration between segregated genders. It attempts to understand the emerging technology practices of workers in higher education institutions, which are aimed at bridging the culturally imposed spatial divide between men and women in the workplace. In examining the gender-segregated context, the study also looks into the consequent organisational and structural changes resulting from technology use. This includes evaluating new practices in terms of progressive change, and how this specifically relates to the work experiences of women as a subordinated and marginalised group.